(untitled) (Research, Society and Development, 2022)
The Mathematics discipline presents difficulties in its teaching-learning process, especially with regard to geometry. Therefore, the present research aims to discuss the reasons why geometry is considered a difficult discipline to learn; to provoke reflections about the use of the history of geometry in the teaching and learning process of this area; and to subsidize the teaching work in relation to the Pythagorean Theorem content. This is a qualitative research and is configured as a bibliographic survey, which used studies by Eves (1992), Boyer (2012) among others, as well as the National Curriculum Parameters. In summary, it is noted that the way in which geometry is approached in the classroom is one of the reasons why this content is difficult to learn. We believe that the use of history as a teaching methodology favors the introduction of geometry content, as the student perceives that the content derives from human construction.